2003
DOI: 10.1007/s10038-003-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis suggests a locus of ichthyosis vulgaris on 1q22

Abstract: Ichthyosis vulgaris (IV) is an inherited scaling skin disorder with a prevalence estimated at 2.29% in China. The gene responsible for this disorder has not been elucidated. To find the disease gene, we ascertained two Chinese IV families. Linkage analysis identified an IV locus on chromosome 1q22 with a maximum twopoint Lod score of 2.47 at D1S1653 (h=0.00). Haplotype analysis placed the critical region in a 7-cM interval defined by D1S1653 and D1S2675. These results provide the basis for further identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Genetic linkage analyses on IV families mapped FLG to the epidermal differentiation complex on chromosome 1q21 12,13 . More recently, genotyping showed that loss‐of‐function mutations in the FLG gene are the cause of IV, 8 and that the condition is inherited in a semidominant manner with 83–96% penetrance 14–16 .…”
Section: Ichthyosis Vulgaris Is Defined By Mutations In Flgmentioning
confidence: 99%
“…Genetic linkage analyses on IV families mapped FLG to the epidermal differentiation complex on chromosome 1q21 12,13 . More recently, genotyping showed that loss‐of‐function mutations in the FLG gene are the cause of IV, 8 and that the condition is inherited in a semidominant manner with 83–96% penetrance 14–16 .…”
Section: Ichthyosis Vulgaris Is Defined By Mutations In Flgmentioning
confidence: 99%
“…The flaky tail phenotype is caused by a single autosomal recessive mutation that maps to mouse chromosome 3, 24 close to the genes encoding mouse loricrin and profilaggrin 25 . Linkage analysis in humans suggested linkage of ichthyosis vulgaris to chromosome 1q22 in two Chinese families 26 . Another study reported linkage of a clinical subtype of ichthyosis vulgaris with an absent granular epidermal layer to the chromosomal region containing the EDC 27 …”
Section: Role Of the Epidermal Differentiation Complex In The Pathogementioning
confidence: 99%
“…Genetic linkage analyses on IV patients mapped the FLG gene to the epidermal differentiation complex on chromosome 1q21 [ 18 ]. Loss-of-function mutations of the FLG gene have been identified to underlie IV, which is inherited in a semi-dominant model with 83–96% penetrance where heterozygotes have mild sub-clinical phenotype compared with homozygotes who with more prominent ichthyosis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%